Pengaruh Variasi Baffle Spacing dan Flow Rate Terhadap Efektifitas Heat Exchanger Shell and Tube Menggunakan Metode NTU (Number of Transfer Unit) dan HTRI - Aji Abdillah Kharisma; Wisnu Malik Pangestu (Universitas Sriwijaya, 2021)
The research was conducted by redesigning the shell-and-tube MOES C heat exchanger by PT. Krakatau Steel, using the HTRI application to find the effectiveness value (E > 0.5). The flow type is counterflow, double segmental type baffles, two tube passes with water, oil fluid, and baffle spacing are 60 mm, 90 mm, and 100 mm, flow rate 5,716 kg/s, 5,781 kg/s, and 5,808 kg/s. The increase in flow rate on the Heat Exchanger results in a decrease in effectiveness, on the contrary, at the minimum flow rate in the Heat Exchanger there is an increase in effectiveness. The greater the number of baffles in the Heat Exchanger, the greater the value of the pressure drop, which results in a decrease in heat transfer at the Heat Exchanger. The higher the flowrate, the greater the heat transfer value, but also the greater the mass and the greater the value of pressure drop that occurs in the Heat Exchanger. The large number of baffles and flowrate also affects the pressure drop and heat transfer values.